THE MELTING POT OF LEGAL SYSTEMS IN INDONESIA (READING THE LEGAL POLITICS OF INDONESIAN ISLAMIC LAW) - Andi Nuzul (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2013)
Islamic law is integrated into but stands independently from Indonesia’s national law. It is integrated in the sense that its substance has been absorbed into the legal systems through laws and other legal rulings and binds all Indonesian citizens. It is independent however, in the sense that its substance governs the internal conduct of Muslims. Islamic law has strengthened the Unitary State of the Republic of Indonesia, especially after the amendments of the 1945 Constitution, whose legal system is not onlybased on the idea of a rechtsstaat or rule of law, but is also based upon elements of religious laws. Hukum Islam dalam sistem hukum nasional Indonesia bersifat integratif dan mandiri. Integratif berarti materi atau substansi hukumnya masuk menjadi bagian produk peraturan perundang-undangan, bersifatmengikat (imperatif) untuk seluruh warga negara. Bersifat mandiri, manakala materi atau substansihukumnya bersifat mengatur secara interen kalangan umat Islam. Hukum Islam menguatkan NegaraKesatuan Republik Indonesia terutama pasca amandamen UUD tahun 1945, sistem hukumnya tidak hanya berlandaskan pada prinsip negara hukum rechtsstaat ataupun the rule of law, tetapi juga berlandaskan pada unsur-unsur dari hukum agama.